Comparison of the developmental tests Bayley-III and Bayley-II in 7-month-old infants born preterm - Reuner, Gitta; Wittke, Andrea; Löpprich, Martin; Pietz, Joachim (European journal of pediatrics, 2013)
The study aims on comparing Bayley Scales of infant development third (Bayley-III) and Bayley second (Bayley-II) edition with special focus on patterns in the first year of life. Fifty-five premature infants (43 with low birth weight/LBW >1,499 g and 12 with very/extremely low birth weight/VLBW/ELBW <1,500 g) aged 7 months (corrected for prematurity) were assessed with the complete Bayley-III. From this assessment, Bayley-II results were retrospectively estimated. Bayley-III results were compared to the expected mean with one-sample t-tests. The mean scores of both editions were compared with the aid of paired-sample t-tests. Pearson correlations between subscales and editions were analysed. The Bayley-III cognitive score of the study group was significantly higher than the expected mean of the standardization sample. VLBW/ELBW had significantly lower motor scores than LBW in both editions. When compared to estimated Bayley-II scores, all relevant Bayley-III scores were significantly higher (all p < .01) with highest difference (ten points) between the motor scales of both editions. There were significant correlations not only between Bayley-III cognitive and language scales but also between language and motor scales. Given the strong association between motor and cognitive behaviour in early infancy, this age-specific pattern is heightening the risk of failure to identify infants at risk for both cognitive and motor delay. Therefore, assessment of infants should comprise all subscales. Since Bayley-III probably overestimates especially motor performance in young infants, when interpreting Bayley-III scores in this age, comparison groups are highly recommended until further validation of normative data are outstanding.